vp100813_elic_NominalForms_dual_questions - Валентина Пуяковна Силкина (Надер); Олеся Ханина (Bernard Comrie, 2010)
O.Khanina collects with V.P.Nader answers to two minor questions about Dualis on the example of the word kaza 'grandma': possibility of *-biq instead of -jq 'SG.NOM.1SG', possibility of *-xi 'DU' in possessive forms, possibility of *-nO instead of -n'iq 'DU.OBL.1SG' тундровый энецкий, русский Language_Name: Enets Language_Region: Asia Language_Country: Russia Project_Status: Complete Year: 2007 Start_Date: 2008-02-01 End_Date: 2011-01-31 Title vp100813_elic_NominalForms_dual_questions